2015
DOI: 10.2147/ott.s86743
|View full text |Cite|
|
Sign up to set email alerts
|

Significance of downregulation of renal organic cation transporter (SLC47A1) in cisplatin-induced proximal tubular injury

Abstract: Background/aimTo elucidate the mechanism responsible for developing acute kidney injury in patients with diabetes mellitus, we also evaluated the issue of whether advanced glycation endproducts (AGEs) influence the expressions of multi antimicrobial extrusion protein (MATE1/SLC47A1) in tubular cells.Materials and methodsTo detect changing expression of MATE1/SLC47A1 in dose- and time-dependent manners, human proximal tubular epithelial cells were incubated with AGE-aggregated-human serum albumin. As a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Indeed, we found that the administration of cisplatin to MATE1-deficient mice was associated with increases in several commonly used biomarkers of drug-induced acute kidney injury, including blood urea nitrogen (BUN) and neutrophil gelatinase-associated lipocalin (NGAL) compared with the values observed in wild-type mice (Supplemental Figure S1). These findings are consistent with prior observations in similar geneticallyengineered mouse models [54][55][56] or studies involving the administration of cisplatin together with inhibitors of MATE1 [57,58], and are in line with observations made in patients receiving treatment with cisplatin who carry impaired function variants in SLC47A1, the gene that encodes MATE1 [59][60][61].…”
Section: Modulation Of Oxaliplatin Pharmacokinetics By Tki Treatmentsupporting
confidence: 92%
“…Indeed, we found that the administration of cisplatin to MATE1-deficient mice was associated with increases in several commonly used biomarkers of drug-induced acute kidney injury, including blood urea nitrogen (BUN) and neutrophil gelatinase-associated lipocalin (NGAL) compared with the values observed in wild-type mice (Supplemental Figure S1). These findings are consistent with prior observations in similar geneticallyengineered mouse models [54][55][56] or studies involving the administration of cisplatin together with inhibitors of MATE1 [57,58], and are in line with observations made in patients receiving treatment with cisplatin who carry impaired function variants in SLC47A1, the gene that encodes MATE1 [59][60][61].…”
Section: Modulation Of Oxaliplatin Pharmacokinetics By Tki Treatmentsupporting
confidence: 92%
“…Tubular injury is a key pathology associated with the nephrotoxic effects of cisplatin. Tubular injury promotes reduced GFR and therefore delayed urinary excretion of cisplatin, leading to platinum accumulation within the tubules [ 83 ]. Given the pathogenesis linked to platinum accumulation in PTEC, increasing the expression of cisplatin efflux transporters has been a molecular target against CIAKI.…”
Section: Pharmacological Approaches Targeting Cisplatin Cellular Ementioning
confidence: 99%
“…It is possible that an increase in MRP expression might be seen in models of nephrotoxicity; however, no studies are yet to present data investigating this. In addition to MRPs, multi-antimicrobial extrusion protein 1 (MATE1/SLC47A1) is suggested to be involved in platinum accumulation associated with cisplatin treatment [ 83 ].…”
Section: Pharmacological Approaches Targeting Cisplatin Cellular Ementioning
confidence: 99%
See 2 more Smart Citations